Behavioral disorders in children born with infertility treatments compared with children born with natural methods - Fatemeh Iranmanesh; Ali Mehdizadeh Zare Anary; Victoria Habibzadeh (Islamic Azad University, 2015)
Introduction: The aim of this study was to investigate behavioral disorders in children born with infertility treatments and children born with normal fertility. Childhood is the most important stage of life in which a person's personality is founded and formed and any neglect of that can lead to problems and conflicts after the childhood. Methods: The present study was a causative and comparative survey. The target statistical population of this study included children born with assisted reproductive techniques and the ones born with natural methods of fertility. The samples of this study were gathered randomly from 30 children born with assisted reproductive techniques in cases in IVF ward in Kerman Afzalipour hospital. After homogenizing the children born with natural methods of fertility with the first group based on gender, age, education level, father's occupation, and family members, 30 subjects were selected. For data collection, Quay and Peterson revised checklist was used which is a standard instrument. To describe the data, descriptive statistics such as mean, standard deviation and frequency were used and inferential statistics were applied to compare the means and independent t test was used to investigate the data. Results: The obtained results showed a significant difference between the behavioral disorders and its components including attention-immaturity and anxiety-reticence, but there was no significant relationship between elements of aggression and conduct disorder. Conclusion: This study showed that the kind of fertilization effective on behavioral disorders in children.